Sexual Self-Concept through a Cross-Cultural Lens: Qualitative Case Studies of Iranian-American Women - Rashidian, Mitra; Minichiello, Victor; Hussain, Rafat (Advances in Social Sciences Research Journal, 2015)
Abstract Recently scholars have examined more closely the topic of female sexual self-concept as an aspect of sexual well-being. Few studies have focused on migrated women’s life experiences cross-culturally, and how that informs a woman’s view of herself as a sexual being. This is particularly true about most middle-eastern cultures, including Iranian-American women. Four case studies draw on qualitative data from interviews with first generation Iranian-American women in the USA to describe the sexual self-concepts evolving as a result of life in both cultures. Applying narrative methodology and feminist theoretical perspectives two themes were revealed. These are i) the influence of family power, and ii) patriarchal social practices. The analysis introduces a multidimensional aspect and process associated with each woman’s view of her sexual self-concept, which takes into account their behaviours, cognitions, and emotions developed in each life stage, and inform her sexual subjectivity (view of herself as a sexual being). Implications of these findings for clinicians and policy makers involved in sexual health care for women are briefly discussed. Keywords: sexual self-concept, cross-cultural, Iranian-American women, sexuality, power relations